VALUE ENGINEERING AND PROJECT COST REDUCTION ON PERFORMANCE OF MIKAP NIGERIA LIMITED, BENUE STATE NIGERIA - Akpen, Fevosun Joyce; Adadu, Akwonya Comfort; Ashiko, Felix Terfa Gaase (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This study examines the application of value engineering in project cost reduction and its impact on the performance of MIKAP Nigeria Limited, Benue State, Nigeria, through the lens of Lean Theory, with Resource-Based View (RBV) and Systems Theory as supporting frameworks. A survey research design was adopted, with a census sampling technique applied to a population of 122. Data were collected using structured questionnaires, with validity confirmed via factor analysis and reliability through Cronbach Alpha statistics. Descriptive statistics and logit regression analysis were used to analyze the data. The results indicate a significant negative relationship between Process Improvement (PIP) and performance, with a coefficient of -1.235, standard error of 0.484, Wald statistic of 6.505, p-value of 0.011, and an odds ratio of 0.291, reflecting a 70.9% decrease in performance likelihood with decreased process optimization. Lifecycle Cost Analysis (LCA) has a coefficient of -1.733, standard error of 0.564, Wald statistic of 9.444, and a p-value of 0.002, showing an 82.3% decrease in performance odds with poor cost management. Quality Assurance (QUA) shows a positive coefficient of 1.652, standard error of 0.461, Wald statistic of 12.846, and p-value of 0.000, with an odds ratio of 5.216, indicating a five-fold increase in performance odds with improved quality assurance practices. This study highlights the importance of continuous process improvement, lifecycle cost analysis, and quality assurance in enhancing organizational performance and offers valuable insights for project cost reduction strategies.